Reporting Non-GAAP Financial Measures A Theoretical and Empirical Analysis in Europe - Moscariello, Nicola; Pizzo, Michele (Cambridge Scholars Publishing, 2020)
The use of alternative performance indicators (APMs) (also known as 'Non-GAAP' earnings) is a widespread phenomenon, and the increased reliance on APMs has recently triggered a strong debate among regulators, managers and investors on the nature of these 'tailored' earnings and on the economic reasons behind them. On one hand, APMs might reflect managers' attempt to offer useful information to predict companies' future sustainable cash-flows and earnings (information hypothesis), while, on the other, the non-standardized nature of these metrics impacts on the comparability of the financial res.